2004
DOI: 10.4049/jimmunol.172.12.7761
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phosphoinositide 3-Kinases by the CCR4 Ligand Macrophage-Derived Chemokine Is a Dispensable Signal for T Lymphocyte Chemotaxis

Abstract: Macrophage-derived chemokine (MDC/CC chemokine ligand 22 (CCL22)) mediates its cellular effects principally by binding to its receptor CCR4, and together they constitute a multifunctional chemokine/receptor system with homeostatic and inflammatory roles in the body. We report the CCL22-induced accumulation of phosphatidylinositol-(3,4,5)-trisphosphate (PI(3,4,5)P3) in the leukemic T cell line CEM. CCL22 also had the ability to chemoattract human Th2 cells and CEM cells in a pertussis toxin-sensitive manner. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 85 publications
(91 reference statements)
9
47
2
Order By: Relevance
“…4). CCL11 and IL-5 are potent inducers of eosinophil development and/or chemotaxis (15), while dendritic cell-produced CCL22 is increased in patients with allergic rhinitis or atopic dermatitis and induces Th2 chemotaxis (41)(42)(43). However, other cytokines might also play a role in the increased eosinophil recruitment and pathology observed in our study.…”
Section: Discussioncontrasting
confidence: 51%
“…4). CCL11 and IL-5 are potent inducers of eosinophil development and/or chemotaxis (15), while dendritic cell-produced CCL22 is increased in patients with allergic rhinitis or atopic dermatitis and induces Th2 chemotaxis (41)(42)(43). However, other cytokines might also play a role in the increased eosinophil recruitment and pathology observed in our study.…”
Section: Discussioncontrasting
confidence: 51%
“…Although the pathways involved in CCL17's effects remain to be elucidated, mechanisms inhibiting Jak/Stat signaling are well defined, e.g., dephosphorylation, proteolytic degradation, or association with inhibitory molecules (48). It is conceivable that CCL17 can interfere with Stat5 phosphorylation by inducing the MAPK pathway, as seen for CCL17-induced interference with Src kinase and ERK phosphorylation, or the PI3K pathway (49)(50)(51). Notably, the putative Stat-inducible gene c-fos was upregulated in T cells after exposure to Ccl17 E/E DCs (A. Zernecke et al, unpublished observations), supporting the hypothesis that CCL17 interacts with growth and differentiation processes through a Stat-dependent pathway.…”
Section: Discussionsupporting
confidence: 49%
“…In lymphocytes, contradictory results have been obtained using PI3K inhibitors (Sotsios et al, 1999;Cronshaw et al, 2004). Moreover, it was recently shown that lymphocyte homing is controlled mainly by DOCK-2 activity, whereas PI3Kγ activation has a minor role in this process (Nombela-Arrieta et al, 2004;Ward, 2004).…”
Section: Discussionmentioning
confidence: 96%